One Person Librarian Strategy in Implementing Knowledge Management in Libraries - Anjani, Afifah; Samosir, Fransiska Timoria; Sa'diyah, Lailatus (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
Bank Indonesia Library in its development in the digital era which is part of Bank Indonesia's transformation in achieving its vision and mission by implementing knowledge management as a valuable asset. In the process where the BI Bengkulu Branch Library adopted One-Person Librarian. This study discusses One-Person Librarian in the strategy of implementing knowledge management of the Bank Indonesia Bengkulu library. Through this study, One-Person Librarian takes strategic steps in the knowledge management process by utilizing the availability of technology that is always integrated with the Bank Indonesia head office library. Although in practice the independence of One-Person Librarian is a challenge in itself. So that there is a need for periodic evaluation of the productivity and effectiveness of One-Person Librarian with the hope that the implementation of knowledge management can be optimized by the organization.Perpustakaan Bank Indonesia dalam perkembangannya di era digital yang menjadi bagian dalam transformasi Bank Indonesia dalam mencapai visi misinya dengan langkah menerapkan manajemen pengetahuan sebagai suatu aset yang berharga. Pada prosesnya dimana perpustakaan Kpw BI Bengkulu mengadopsi One-Person Librarian. Penelitian ini membahas mengenai One-Person Librarian dalam strategi penerapan manajemen pengetahuan perpustakaan Bank Indonesia Bengkulu. Melalui penelitian ini One-Person Librarian mengambil langkah strategis dalam proses manajemen pengetahuan dengan memanfaatkan ketersediaan teknologi yang selalu terintegrasi dengan perpustakaan kantor pusat Bank Indonesia. Meskipun pada prakteknya kemandirian One-Person Librarian menjadi tantangan tersendiri. Sehingga perlunya evaluasi secara berkala terhadap produktivitas dan efektivitas One-Person Librarian dengan harapan penerapan manajemen pengetahuan dapat dioptimalkan oleh organisasi.